2020
DOI: 10.1002/mp.14043
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination analysis of breast calcifications using x‐ray dark‐field radiography

Abstract: Background: X-ray dark-field radiography could enhance mammography by providing more information on imaged tissue and microcalcifications. The dark field signal is a measure of small angle scattering and can thus provide additional information on the imaged materials. This information can be useful for material distinction of calcifications and the diagnosis of breast cancer by classifying benign and malign association of these calcifications. Methods: For this study, institutional review board approval was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
(175 reference statements)
1
6
0
Order By: Relevance
“…Depending on the affected arteries, patients can suffer from coronary or peripheral artery disease, as it was for the patient in our study. Previous studies showed that calcification in the breast is visible in the dark-field image, potentially improving breast cancer detection [56][57][58]. We were also able to see calcification of the arteries in the dark-field image.…”
Section: Discussionsupporting
confidence: 57%
“…Depending on the affected arteries, patients can suffer from coronary or peripheral artery disease, as it was for the patient in our study. Previous studies showed that calcification in the breast is visible in the dark-field image, potentially improving breast cancer detection [56][57][58]. We were also able to see calcification of the arteries in the dark-field image.…”
Section: Discussionsupporting
confidence: 57%
“…Based on phantom and fresh sample measurements, they successfully presented the distinguishability of microcalcifications of type I and II while the dose exceeds the clinical limit. In the following years, however, these results were controversially discussed in the literature [38][39][40]. In 2016, Scherer et al further examined the benefit of the darkfield signal by the investigation of the micromorphology and showed that the diagnostic content is enhanced so that invasive procedures such as biopsies could be reduced [41].…”
Section: Classification Of Microcalcifications Using X-ray Dark-fieldmentioning
confidence: 99%
“…Use cases for X-ray dark-field imaging include the detection and quantification of pulmonary emphysema and imaging of brain connectivity [68,69]. Furthermore, PCI can improve the sensitivity of calcification classification in breast imaging, and clinical systems in the field of mammography are being developed [51].…”
Section: Phase-contrast Imagingmentioning
confidence: 99%